Perancangan Aplikasi Kumpulan Komik Berbasis Android Menggunakan Algoritma Crochemore Perrin - Siregar, Abdul Haris; Hasibuan, Nelly Astuti (STMIK Budi Darma, 2020)
Comic is a work of art that is designed using a collection of still images and is complemented by a text or story. Comics are a reading book needed by children and teenagers alike. In comics, apart from the interesting content of the stories, there are also moral messages embedded in each story. However, with the development of technology, there are many comics whose stories do not educate teenagers' characters, starting from pictures and no more educational moral messages embedded in the stories. The solution drawn from this problem is by designing an Android-based comic application that can be easily accessed and understood by the public, especially teenagers. However, due to the limitations of smartphone applications to present comic episodes, string matching is needed to search for comic titles. The string matching algorithm is a string matching algorithm that looks for a string consisting of several patterns (characters) in a large amount of text. For android-based comic applications, it is designed using the Crochemore-perrin algorithm